Uncoupling of neuroinflammation from axonal degeneration in mice lacking the myelin protein tetraspanin‐2. Issue 11 (30th August 2013) - de, Patricia; Patzig, Julia; Möbius, Wiebke; Barrette, Benoit; Wagner, Tadzio L.; Kusch, Kathrin; Edgar, Julia M.; Brophy, Peter J.; Werner, Hauke B.
<x xml:space="preserve">Abstract</x> Deficiency of the major constituent of central nervous system (CNS) myelin, proteolipid protein (PLP), causes axonal pathology in spastic paraplegia type‐2 patients and in Plp1null‐mice but is compatible with almost normal myelination. These observations led us to speculate that PLP's role in myelination may be partly compensated for by other tetraspan proteins. Here, we demonstrate that the abundance of the structurally related tetraspanin‐2 (TSPAN2) is highly increased in CNS myelin of Plp1null‐mice. Unexpectedly, Tspan2null‐mutant mice generated by homologous recombination in embryonic stem cells displayed low‐grade activation of astrocytes and microglia in white matter tracts while they were fully myelinated and showed no signs of axonal degeneration. To determine overlapping functions of TSPAN2 and PLP, Tspan2null*Plp1null double‐mutant mice were generated. Strikingly, the activation of astrocytes and microglia was strongly enhanced in Tspan2null*Plp1null double‐mutants compared with either single‐mutant, but the levels of dysmyelination and axonal degeneration were not increased. In this model, glial activation is thus unlikely to be caused by axonal pathology, and vice versa does not potentiate axonal degeneration. Our results support the concept that multiple myelin proteins have distinct roles in the long‐term preservation of a healthy CNS, rather than in myelination per se. GLIA 2013;61:1832–1847